2017
DOI: 10.1093/alcalc/agx015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Dependence Severity on Neural Correlates of Delay Discounting

Abstract: Among alcohol-dependent individuals, alcohol dependence severity is associated with overactivation of ventromedial prefrontal areas during delayed and underactivation of dorsolateral prefrontal regions during impulsive reward decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…These differing results may in part be due to the higher average AUD severity in this previous study. As alcohol dependence severity is associated with weakened frontostriatal connectivity and dysregulated activity during effortful decision making (Courtney et al, 2013;Lim et al, 2017), these results suggest that Asp40 carriers with more severe AUD require increased recruitment of frontal systems to regulate striatal reward processing regions.…”
Section: Discussionmentioning
confidence: 93%
“…These differing results may in part be due to the higher average AUD severity in this previous study. As alcohol dependence severity is associated with weakened frontostriatal connectivity and dysregulated activity during effortful decision making (Courtney et al, 2013;Lim et al, 2017), these results suggest that Asp40 carriers with more severe AUD require increased recruitment of frontal systems to regulate striatal reward processing regions.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study reported that alcohol dependence severity was positively associated with activation in paracingulate gyrus and frontal pole in delayed relative to impulsive, immediate decisions (Lim et al ., ). Our results extend those previous findings and demonstrate that the increased recruitment of prefrontal areas, particularly of frontal pole, may indeed be required to delay reward successfully.…”
Section: Discussionmentioning
confidence: 97%
“…First, alcohol dependence symptoms are sometimes associated with higher breakpoints in demand tasks, suggesting dependence is associated with the discounting of price costs (MacKillop et al 2015 ), and student drinkers with a family history of alcoholism are less sensitive to the effect of imagined next-day responsibilities on reducing alcohol demand (Murphy et al 2014 ). Second, alcohol dependence symptoms are associated with a steeper delay discounting of rewards, which could theoretically extend to neglect of future costs associated with alcohol (Lim et al 2017 ; MacKillop et al 2011 ; Petry 2001 ; Vuchinich and Simpson 1998 ). Third, drug users show deficits in reversal learning which could be driven by insensitivity to punishment of the incorrect response during reversal (Ersche et al 2008 ; Fortier et al 2008 ; Reiter et al 2016 ; Vanes et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In these tasks, drinkers choose between smaller immediate and larger delayed rewards (alcohol or money). It is typically found that alcohol use disorder symptoms are associated with a greater preference for the smaller immediate reward (Lim et al 2017 ; MacKillop et al 2011 ; Petry 2001 ; Vuchinich and Simpson 1998 ). One interpretation of this result is that dependence is associated with greater sensitivity to time delay costs (not cost discounting), because the value of the reward declines more steeply with delay.…”
Section: Introductionmentioning
confidence: 99%